Incidence of facial pressure injuries in health‐care professionals during the COVID‐19 pandemic: A systematic review and meta‐analysis. Issue 2 (19th December 2022) - Su, Honghong; Zhou, Wenguang; Kong, Yue; Zhu, Fangfang; Xu, Baoling; Shen, Xianying; Zhang, Weiqin; Zhou, Qijun; Lv, Qian
Abstract: Aim: To evaluate the incidence of facial pressure injuries in health‐care professionals during the COVID‐19 pandemic in a meta‐analysis. Methods: Related studies were obtained through electronic databases, including PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI) Chinese Scientific Journal (VIP) China Biomedical Literature service systems (CBM) and Wanfang Data (from inception to 27 November 2021). The pooled incidence and the 95% confidence interval of facial pressure injuries were calculated with Review Manager v5.4 software. Results: Overall, 16 studies with 14 430 health‐care professionals were included. Pooled results showed that the pooled incidence of facial pressure injury in health‐care professionals was 58.8% (95% CI: 49.0%–68.7%; p < 0.01). The results of the subgroup analysis showed that the incidence of facial pressure injury in these staff was high, and predominantly stage I pressure injury, in the following cases: in health‐care professionals who wore personal protective equipment for longer than 4 h, in those without any training experience, and on the nose. Conclusion: Administrators and researchers should pay attention to preventing facial pressure injury related to the wearing of personal protective equipment (PPE) by ensuring all health‐care professionals receive training and by limiting prolonged periods of use. Summary statement: What is already known about this topic? Facial pressure injury was one of the most common effects experiencedby health‐care professionals wearing facial PPE during COVID‐19, which seriously affected their facial comfort and self‐image. A number of studies have reported the incidence of facial pressure injury in health‐care professionals, but the evidence is inconsistent. Medical staff are the main force during the COVID‐19. What this paper adds? This study showed that the pooled incidence of facial pressure injury in health‐care professionals was 56.8% during COVID‐19. This study showed that there was a higher incidence of facial pressure injury in staff who wore PPE for longer than 4 h and in those without any training experience. This study showed that the nose was the most common part of the face with pressure injury, and Stage I pressure injury was the most prevalent injury type in health‐care professionals. The implications of this paper: This study may provide evidence for managers about the development of guidelines for health‐care professionals to prevent and manage facial pressure injuries and promote the health of health‐care professionals.